Just one more episode: Predictors of procrastination with television and implications for sleep quality - Exelmans, Liese; Meier, Adrian; Reinecke, Leonard; Van Den Bulck, Jan (Mass Communication and Society, 2019)
Sleep experts have raised concern over the effects of electronic media use on sleep. To date, few studies have looked beyond the effects of duration and frequency of media exposure or examined the underlying mechanisms of this association. As procrastinatory media use has been related to lower well-being, we used data from two survey studies (N1 = 821, N2 = 584) to investigate (a) predictors of procrastinatory TV viewing and (b) the link between procrastinatory TV viewing and sleep quality. Findings from both studies indicate that those with a stronger viewing habit, higher TV involvement, and an eveningness preference reported more procrastinatory TV viewing. Procrastinatory TV viewing was related to subjective sleep quality, sleep latency, sleep efficiency, and daytime dysfunction. This association was fully mediated by perceived stress. As sleep is key for the replenishment of self-control, procrastinators may be setting themselves up to fail at self-regulating, a situation exacerbated by the omnipresence of media in today’s society.
CRIS-Team Scopus Importer:2021-02-02